Principles of asymmetrical warfare how to beat Islamo-fascists their own game - Uda, Robert T. (iUniverse, Inc., 2007)
Principles of Asymmetrical Warfare: How to Beat Islamo-fascists at Their Own Game provides principles, strategies, tactics, and methods available to the Administration in winning and ending the wars in Afghanistan and Iraq and the War on Terrorism. Some strategies and tactics appear extreme to a civilized country as the United States. However, we should know about and understand these strategies and tactics in case we must use them because the Isfasts are about to annihilate, conquer, or place us in bondage. I have quoted ideas from Sun Tzu, Gen. George S. Patton, Jr., and Dr. Michael Savage, a man of great intellect. Our Administration has made a major mistake by not learning from great warriors like Sun Tzu and Gen. Patton. Our Administration makes an even larger mistake by ignoring Michael Savage's thoughts, ideas, and suggestions.